Sociodemographic and Clinical Characteristics of Patients With Vertigo at Clínica Occidente de Otorrinolaringología, Medellín, Colombia: A Descriptive Study (2014)
ABSTRACT: Introduction: Vertigo and dizziness account for an estimated 20 to 30 percent of primary care clinic visits, and it is even more common among older adults. To date, there are few papers published about clinical characteristics of individuals with balance disorders. In Colombia there is no data about this issue. A good anamnesis and physical examination can be done in most of the cases, which are mandatory aspects to achieve a successful diagnosis and treatment of this disorder. Objetives: To describe the sociodemographic and clinical characteristics in outpatients with vertigo at Clínica Occidente de Otorrinolaringología (Medellín, Colombia) between October of 2010 and March of 2013. Methods: Clinical charts of the patients older than 18 with vertigo and balance disorders were reviewed in an attempt to determine several variables including sex, age, clinical characteristics and symptoms improvement. Results: One hundred and thirty-four patients were included. The mean age was 57.43 years. Most patients were female (76.9%). The most common complaints were vertigo (85.8%), balance disorders (67.8%) and head fullness sensation (46.3%). The median time between onset and first consultation was 36 months (P25: 6, P75: 120). Fifty-three percent of the patients used vestibular suppressants more than three months before the first consultation, and 81.3% used them less than three months before. The definitive diagnoses were benign paroxysmal positional vertigo (38.8%), vestibular suppressants-associated vertigo (25.4%), migraineassociated vertigo (7.5%), Meniere’s disease (5.2%), and other disorders (23.1%). All vestibular suppressant drugs were discontinued in 71.6% of the cases. In more than 60% of the cases, a concordance between the first consultation diagnosis and definitive diagnosis was found. Clinical improvement was achieved in 56.7% of the cases with an increasing successful rate (69.18%) at the end of the treatment. Conclusions: Vertigo is more common in female patients regardless of cause. The most frequent diagnoses were benign paroxysmal positional vertigo and vestibular suppressants-associated vertigo. In the last one the more common symptom was the balance disorder in contrast to all other diagnoses in which vertigo was the predominant symptom. All patients in this study had chronic progression of symptoms, and most of them were using vestibular suppressants at the time of the first consultation. This finding implies that drugs to treat vertigo are being taken indiscriminately, which affects the diagnosis, control and improvement of the patients. Further studies are needed to assess the outcomes indicators in vertigo.